Validation of quality of life instruments in Adolescents with facial Acne Vulgaris in Ibadan, Nigeria: any influence of social class - Anaba, Ehiaghe Lonia (The Nigerian Health Journal, 2019)
Background: Studies have revealed diminished quality of life (QOL) in adolescents who have facial acne vulgaris. Generic and disease specific QOL questionnaires are used for this QOL assessment. These documents have not been cross-validated in Nigeria. Aims and Objectives: This study aims to Cross-validate the Cardiff Acne Disability Index (CADI) and the Children’s Dermatology Life Quality Index (CDLQ), determine if acne impairs the QOL of Nigerian adolescents and the socio-demographic (age and social class of the adolescents) factors that influence this QOL. Methodology: This was a cross-sectional population based study of 574 students aged 9-20 years from four co-educational secondary schools with two private schools representing the high socioeconomic class and two public schools representing the low socioeconomic class. QOL was assessed using the CADI and the CDLQ questionnaires and a questionnaire for socio-demographic data was administered. Data was analyzed with SPSS 16. Results: A total of 574 students were studied, 48.9% males and 51.0% females. The CADI and the CDLQI correlated fairly with a Spearman’s rho co-efficient of 0.522. The median CADI was 2 with an inter-quartile range of 4 and the median CDLQI score was 1.00 with an inter-quartile range of 3.75. Median CADI score was 2 (4.00) in both high and low socio-economic classes Correlation between age and CADI was poor with a Spearman’s coefficient of 0.078. Conclusion: Both QOL instruments correlated well and can be used for QOL assessment in Nigerian adolescents who have facial acne vulgaris.